The pre-participation examination in a COVID-19 world - Malek, K. (Pediatric nursing, 2021)
As children and adolescents become vaccinated and return to sports, parental concerns arise on how to safely return to play. Many athletes are required to undergo a standardized pre-participation examination at their pediatric primary care provider prior to participating in sports. The pre-participation examination`s purpose is to evaluate the athlete`s physical and psychological health, as well as any pre-disposing factors that could potentially impact the athlete`s condition. Prior to the COVID-19 pandemic, the Illinois High School Association (IHSA) pre-participation form included a physical examination, patient history questionnaire, and questions surrounding family history. The form has now been updated to include supplemental COVID-19 questions (IHSA, 2021). Parents often rely on the pediatric nurse`s expertise when completing the pre-participation health form and may have questions, such as whether to list a prior COVID-19 infection on the health form or how the provider will evaluate that their child is fit to participate in sports. Ultimately, the nurse should feel comfortable answering these questions and providing guidance to their patients and families. When providing counseling to parents and athletes, the nurse should emphasize the multiple factors that impact eligibility. The disease burden in the community, the overall health o f the athlete, the living environment, and each athlete`s network of friends and family members who have comorbid conditions should be factors to think about when considering participation (Diamond et al., 2021). Ultimately, the health care team must ensure all required testing is complete before the athlete can jump back into the world of sports.